Comparison of Frequency Vaginal and Cesarean Deliveries - K Karami; M Najafian; P Shahri; S Faizi; Z Noorifard (Tehran University of Medical Sciences, 2009)
"nBackground: We investigated the rate of vaginal childbirth and Cesarean and its causes in maternity wards of Imam Khomeini Educational Hospital in Ahwaz the capital city of Khuzestan Province and Al- Hadi Hospital in Shoostar as a traditional city."nMethods: In this comparative descriptive study data were obtained from medical records of birth deliveries in six months (March to September) in year 2007. Data were analyzed using SPSS software."nResults: The results show a total rate of 29% Cesarean and 71% vaginal childbirth in hospitals. The rate of Cesarean in Imam and Al -Hadi Hospitals was 23% and 33%, respectively. The main cause of Cesarean in Imam and Al-Hadi Hospitals was failure of labor progression (35% and 33%, respectively). Most Cesarean s were occurred in an age range of 20-25 yr."nConclusion: Comparing with international acceptable rate (20-22%), Cesarean rate in both hospitals was high. It seems special attention should be made by persons, committees or organizations in charge of community health to child birth practices in both hospitals.